Semiconductor Nanoparticles: A Versatile Route to Assemble Semiconductor Nanoparticles into Functional Aerogels by Means of Trivalent Cations (Small 16/2020). Issue 16 (23rd April 2020) - Zámbó, Dániel; Schlosser, Anja; Rusch, Pascal; Lübkemann, Franziska; Koch, Julian; Pfnür, Herbert; Bigall, Nadja C.
Abstract : In article number 1906934, Nadja C. Bigall and co‐workers report a non‐oxidative and versatile route to assemble semiconductor dot‐in‐rods and core/crown nanoplatelets into hyperbranched, voluminous and fluorescent gel structures by using trivalent cations. Due to the crystal‐to‐crystal connection between the nanoscopic building blocks in the network, the enhanced charge carrier mobility can be utilized in electrocatalytic applications upon illumination.